Efektivitas BPOM dalam Pengawasan Peredaran Produk Snack Reject sebagai Upaya Perlindungan Konsumen di Indonesia - Rivaldy Amanda Saputra; Baidhowi (CV Rewang Rencang, 2025)
This research examines the effectiveness of the Food and Drug Supervisory Agency (BPOM) in monitoring the circulation of reject snack products in Indonesia within the context of consumer protection. The method employed is a qualitative approach with empirical legal research. Data were collected through interviews with BPOM officials and business actors on e-commerce platforms, observations of reject snack product sales practices, and documentation of relevant regulations. The results indicate that BPOM's supervision of reject snack products is not optimal, due to limitations in reaching all areas of circulation, especially in informal markets and digital platforms. Additionally, many products sold do not include complete information regarding composition and expiration dates, which may violate consumer rights. This study recommends the need for strengthening regulations related to reject products and increasing consumer awareness of potential risks.